Variabel Brand Image yang Mempengaruhi Keputusan Pembelian Telepon Seluler (Ponsel) Nokia - Tin Agustina Karnawati; Andoni Qoiru Cokro (Universitas Negeri Surabaya, 2018)
Increasingly rapid development of communication technology, especially cellular phones. Cellular phones becomes a very important thing to facilitate communication. Nokia as one of the leading companies in telecommunications have to think of a strategy to win market share there. One strategy is to brand image that can provide a positive influence on purchase decisions Nokia mobile phone. This reseach aimed to find influence of brand image that consists of a sub-variable corporate image, user image, and product image to the cell phones Nokia buying decision on student STIE Asia Malang either partially or simultaneously. The data was collected by distributing questionnaires to students STIE Malang Asia are divided into 87 people. Answer of respondents processed using multiple linear regression analysis, t test, F test, and determination coefficient (R2). Based on the results of t test analysis of variables known that sub-variable corporate image (thitung = 3.529), user image (thitung = 3.637), and product image (thitung = 4.518). Sub variables that have a dominant influence is the product image. From the test results of the F value is known Fhitung = 28. 299 (significant F value = 0.000). This means that the partial and variable simultaneous brand image consists of a sub-variable corporate image, user image and product image significantly influence purchasing decisions on student Nokia cell phones STIE Asia Malang. R2 value is found to be 50.6%, meaning that the variable purchasing decisions of cell phones Nokia on student STIE Asia Malang influenced by sub-variable corporate image, user image, and product image by 50.6%, while the remaining 49.4% are influenced by variables outside brand image variables.